Advanced γ-Ray Emission Studies of G15.4+0.1 with Fermi-LAT: Evidence of Escaping Cosmic Rays Interacting with Surrounding Molecular Clouds - Yuan Li; Yuliang Xin; Siming Liu; Yu He (The Astrophysical Journal, 2023)
We present an analysis of γ -ray emission in the direction of supernova remnant (SNR) G15.4+0.1 with 13 yr Fermi Large Area Telescope data. There are three point-like GeV sources in this region: one is spatially coincident with the TeV source HESS J1818-154 and is interpreted as the counterpart of HESS J1818-154. Its γ -ray spectrum can be well fitted by a single power law with an index of 2.3. The other two sources with log-parabola spectra are spatially coincident with dense regions of surrounding molecular clouds revealed by CO observations. Their γ -ray emission originates from hadronic π ^0 decay due to inelastic collisions between nuclei in the clouds and cosmic rays accelerated in and escaping from SNR G15.4+0.1. The total energy of the escaping protons is about 10 ^48 erg, assuming a point-like instantaneous injection. However, the inferred diffusion coefficients are lower than the typical Galactic value.